Pengaruh Latihan Five Dot Drill Terhadap Peningkatan Kelincahan - Dwitama, Rizki Septa putra; Sutisna, Nana; Rohendi, Andang; Rustiawan, Hendra (Universitas Galuh, 2024)
This research aims to determine whether there are positive changes in body agility as a result of the five dot drill treatment. The research method used is pre-experimental design. The research location is at SMK YPS 1 Ciamis Regency. The research subjects were 20 people. The sampling technique is total sampling. Based on data analysis using SPSS series 24, the results of data processing were,